Proposal:Step by Step Procedures of Scanning Document Directly to Email (Printer Ricoh 907ex) - Johari, Mohd Helmi; Ayob, Mohd Fairullazi (2015)
Advantages: To reduce paper costs To save storage and working space The document scanning can be send direct to personal email, the fastest way for the document to travel. The document scanning can be accessed online at everywhere and anytime using digital devices, i.e. smart phone, table, computer, laptop, etc. The document scanning can be easily save in soft-copy backups Friendly user and self-service To reduce long distance fax charges.